0
$\begingroup$

Find the derivative of the function:

$$\frac {x^2}2 \cdot (I[x \ge 0] - I[x < 0])$$

Using the limit definition:

$$\lim_{h \to 0} \frac {f(x+h) - f(x)}{h}$$

Now at a simple glance, I know the derivatives of this is the absolute value function ($x \cdot (I[x \ge 0] - I[x < 0])$) as I obtained the other function through integration. My trouble here is that I cannot the algebraic steps for evaluating the limit.

I found that I could restructure the function as:

$$\frac {x^2}2 \cdot (I[x \ge 0] + 1 - I[x < 0] - 1)=$$

$$ \frac {x^2}2 \cdot (I[x \ge 0] + I[x\ge 0] - 1)=$$

$$ x^2 \cdot I[x \ge 0] - \frac {x^2}2$$

I'm not sure if that is easier to take the derivative of. It looks like it might be.

$\endgroup$
2
$\begingroup$

At any point other than $0$, this derivative is as easy to prove as finding $x^2$'s:

If $x < 0$:

$$f'(x) = \lim_{h \to 0} \frac {f(x+h) - f(x)}{h} = \lim_{h \to 0} \frac {\frac{-(x+h)^2}2 + \frac{x^2}2}{h} = \lim_{h \to 0} \frac {xh + \frac{h^2}2}{h} = x$$

If $x > 0$:

$$f'(x) = \lim_{h \to 0} \frac {f(x+h) - f(x)}{h} = \lim_{h \to 0} \frac {\frac{(x+h)^2}2 - \frac{x^2}2}{h} = \lim_{h \to 0} \frac {-xh + \frac{h^2}2}{h} = -x$$

Finally, if $x = 0$:

$$f'(0) = \lim_{h \to 0} \frac {f(0+h) - f(0)}{h}$$

$$\lim_{h \to 0^+} \frac {f(0+h) - f(0)}{h} = \lim_{h \to 0^+} \frac {\frac{-(0+h)^2}2 - \frac{0^2}2}{h} = \frac12\lim_{h \to 0^+} \frac {-h^2}{h} = 0$$

$$\lim_{h \to 0^-} \frac {f(0+h) - f(0)}{h} = \lim_{h \to 0^-} \frac {\frac{(0+h)^2}2 + \frac{0^2}2}{h} = \frac12\lim_{h \to 0^-} \frac {h^2}{h} = 0$$

Therefore, $f'(0) = 0$

And by their powers combined...

$$f'(x) = x * (I[x >= 0] - I[x < 0]) = abs(x)$$

Edit: As Did said, indicator functions are defined case by case so sometimes it's not possible to work with them without splitting. That said, there is a way to obtain $f'(x)$ with a little less surgery. As in:

$$f(x) = \frac12 abs(x)x$$

$$\frac{df(x)}{dx} = \frac{d(\frac12 abs(x)x)}{dx} $$

Now, for $x \ne 0$, we can express the derivative of $abs(x)$ as $\frac{abs(x)}x$, so:

$$\frac{d(\frac12 abs(x)x)}{dx} = \frac12\left[ x\frac{d(abs(x))}{dx} + abs(x)\frac{dx}{dx} \right] = \frac12\left[ x\frac{abs(x)}{x} + abs(x)\right] = abs(x)$$

And then for $x=0$ we proceed as before.

$\endgroup$
  • $\begingroup$ But how would it be solved without splitting it? I don't want it solved case by case. I want to know how the entire expression can be reduced... $\endgroup$ – The Great Duck Jun 12 '16 at 2:50
  • $\begingroup$ "I don't want it solved case by case" Why? Note that this is an odd requirement, starting from a function very much defined "case by case". $\endgroup$ – Did Jun 12 '16 at 14:04
  • $\begingroup$ @Did Becuase I want to know the limit identities regarding indicator functions used in solving it. $\endgroup$ – The Great Duck Jun 15 '16 at 20:46
  • $\begingroup$ @Emisor I see though... I guess whatever direct identity comes into play is too complex for our minds to grasp. Either that, or the identity is the derivation result. $\endgroup$ – The Great Duck Jun 15 '16 at 20:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.